(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Background: The present study assessed the managerial capabilities of autopsy surgeons in India in future response as preparedness to disaster. The need for this was further highlighted by various disasters or similar situations that have been witnessed by the mankind during the 21st century, including the ongoing Covid-19 pandemic, with its latest variant of concern “Omicron”. Aims and objectives: To provide literature related to mass fatality management related benchmarks, and correlates of actual preparedness as a response to a future disaster, and suggest action plan (if any) in the light of the results. Materials and Methods: This cross sectional study was conducted as an anonymous survey by utilizing a pre tested and validated self-administered questionnaire that was made available via electronic mail to the study